Pengaruh Terpaan Kanal Jonathan terhadap Minat Beli Skin pada Game Mobile Legends (Kasus Instagram Jonathan Liandi) - Erlangga Yudha Satria; Diana Amaliasari (LPPM Institut Pendidikan Nusantara Global, 2026)
This study investigates the influence of YouTube content from the Jonathan Liandi channel on purchase interest in Mobile Legends skins. Known among gamers as both entertainment and a source of information on in-game items, the channel delivers engaging and humorous content. Using a quantitative approach and the Uses and Effects theory, the research involved 100 Mobile Legends players selected with the Slovin formula, measuring media exposure through frequency, duration, and depth of attention, and purchase interest from cognitive, affective, and conative aspects. Analysis using mean score calculation, classical assumption tests, and simple linear regression revealed a positive and significant influence, with an R Square of 18.9%, indicating that the content explains part of the variation in purchase interest while the rest is influenced by other factors, confirming that YouTube content can meaningfully affect audience behavior.